Communauté de prisonniers, prisonniers de la communauté : négocier le pouvoir dans les prisons parisiennes du XVIIIe siècle - Sophie Abdela (Les Cahiers de Framespa)
This article explores the dynamics which governed the relationships between men in the Parisian prisons of the 18th century. It highlights the strategies, transactions, and maneuvers which were at the prisoners’ disposal and allowed them to assert themselves as a community. Thus unified, the prisoners no longer limited themselves to enduring their imprisonment: they dared to claim and challenge as one entity. This common position may even have given them, at times, the power to reform the prison world more largely.